Stress Hyperglycaemia Indicates Embolus Size and Localization in Patients with Acute Pulmonary Embolism - Velimir Altabas; Lucija Pukec; Stella Mlinarić; Hrvoje Pintarić; Aljoša Šikić (International Journal of Endocrinology)
Objective. Acute pulmonary embolism is a life-threatening form of venous thromboembolism often causing stress hyperglycaemia. The aim of this study was to determine the prognostic value of stress hyperglycaemia in acute pulmonary embolism, providing new insights into the presumed embolus size and localization, clinical parameters (Pulmonary Embolism Severity Index, PESI), and in-hospital mortality. Design and Methods. Among a total of 95,454 patients referred to the Emergency Department of the Sestre Milosrdnice University Hospital Centre between 2014 and 2016, all patients with acute pulmonary embolism were included into this observational cohort study. The study group consisted of 190 patients aged 25–96. Relevant patient history, clinical data, and laboratory findings were collected during the entire hospitalization period. Data were analyzed for the entire group of patients, as well as separately for patients without diabetes, using the Fisher exact test and logistic regression. Results. Analysis of embolus localization as an indirect parameter of embolus size showed that patients with stress hyperglycaemia more often had emboli located in proximal parts of the pulmonary circulation (i.e., main artery or lobar branches) (p<0.05). Furthermore, stress hyperglycaemia correlated with PESI score and diabetes (p<0.05) in the entire patient group. Stress hyperglycaemia showed independent association with in-hospital mortality in patients (p<0.05). Conclusion. Stress hyperglycaemia in patients with acute pulmonary embolism is associated with embolus localization in larger arteries of the pulmonary circulation and higher PESI score and therefore could serve as an independent in-hospital mortality predictor.